Haruskah Melakukan Survey Ulang ? Evaluasi Metode Pemutakhiran NJOP Bumi PBB-P2 di Kota XYZ - Yusron Hilmy; Yulianti Abbas (IQTISHODUNA, 2023)
The purpose of this study is to evaluate the use of Land Value Zone (Zona Nilai Tanah/ZNT) re-survey method in updating the Sale Value of Tax Object (Nilai Jual Objek Pajak/NJOP) Bumi at XYZ City. Using three criteria from Adam Smith’s the Four Maxims, namely equity, certainty and economics of collection, this study assesses whether the re-survey method is appropriate. This study uses descriptive method, case study strategy and a mixed approach (quantitative and qualitative) by examining changes in the current NJOP Bumi with the results of the ZNT survey for the last 3 (three) years as well as interviews. This study finds that, based on the existing regulation, the determination of the NJOP Bumi carried out by conducting a ZNT survey meets the criteria of equity and certainty. However, ZNT surveys require considerable resource mobilization, and the implementation is not simple. Additionally, the results of the data analysis and interview indicate the lack of pattern in the NJOP value changes. As a result, the re-survey method is appropriate to update the NJOP. In conclusion, by applying the re-survey method, the XYZ City Government prioritizes the equity and certainty criteria of the Four Maxims over the economics of collection.